Thunder from the sea - Harlow, Joan Hiatt (New York : Margaret K. McElderry Books, 2004)
Just when his dreams of being part of a family and having a dog seem to be coming true, Tom wonders if trouble with neighbors on his new island home and the impending birth of a new baby will change everything. Set in Newfoundland in 1929.
700L
Accelerated Reader AR
Accelerated reader
edited hb 2015-06-16
Keywords: Orphans; Dogs; Family life -- Newfoundland and Labrador; Newfoundland and Labrador; Newfoundland and Labrador; Fiction; Fiction